2017
DOI: 10.1038/s41598-017-07605-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of RNAi method for screening candidate genes to control emerald ash borer, Agrilus planipennis

Abstract: The ingestion of double-strand RNAs (dsRNA) targeting essential genes in an insect could cause mortality. Based on this principle, a new generation of insect control methods using RNA interference (RNAi) are being developed. In this work, we developed a bioassay for oral delivery of dsRNA to an invasive forest and urban tree pest, the emerald ash borer (EAB, Agrilus planipennis). EAB feeds and develops beneath the bark, killing trees rapidly. This behavior, coupled with the lack of a reliable artificial diet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…Similar to the induction of the lethal effect of diap1 f-RNAi in previous studies 21,23,24,25 , we showed that in H. vigintioctopunctata , the effect of diap1 f-RNAi on feeding disorder has dose-sensitivity for dsRNA (Fig. 2d).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to the induction of the lethal effect of diap1 f-RNAi in previous studies 21,23,24,25 , we showed that in H. vigintioctopunctata , the effect of diap1 f-RNAi on feeding disorder has dose-sensitivity for dsRNA (Fig. 2d).…”
Section: Discussionsupporting
confidence: 88%
“…3). This lethal effect is rapid compared to that of the previous study in A. planipennis (10 days for 78% mortality) 24 . Since all of the diap1 f-RNAi larvae were dead within 1-4 days after the feeding cessation, this rapid lethality may have occurred as a result of the acute feeding cessation, either indirectly or directly.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…11,49,50 The level of sensitivity to RNAi by microinjection and oral exposure can be variable among insects within the same order. For example, in the Coleoptera order, D. virgifera virgifera, T. castaneum, Leptinotarsa decemlineata, Meligethes aeneus, Rhynchophorus ferrugineus, C. puncticollis, C. brunneus and A. planipennis are sensitive to both methods of dsRNA delivery, 29,30,49,[51][52][53][54][55] whereas Anthonomus grandis, Anthonomus eugenii and Aethina tumida are recalcitrant to RNAi by oral exposure. [56][57][58] These studies demonstrate the importance of evaluating the RNAi sensitivity by microinjection as well as by feeding in the target insect species since it is not possible to predict the RNAi effectiveness based on the RNAi response found in other insects, even in closely related species.…”
Section: Discussionmentioning
confidence: 99%